THE RELATIONSHIP OF FAMILY SUPPORT WITH COMPLIANCE WITH POST STROKE MEDICATION IN ELDERLY AT HOSPITAL - Rita, Friska Prima; Syamsuddin, Fadli; Febriona, Rona (PT. Nursing Genius Care, 2024)
Stroke is a cerebrovascular disease (brain blood vessels) that is characterized by impaired brain function due to damage or death of brain tissue due to blockage of blood and oxygen flow to the brain. This study aimed to determine the relationship between family support and adherence to taking medication after stroke in the elderly. This research design uses an analytical survey with a cross-sectional approach. Sampling, using Accidental Sampling, obtained 30 respondents. The research results show that family support in caring for elderly people suffering from post-stroke disease is 40% in the good category and 60% in the poor category. Compliance with taking medication in post-stroke patients was 33.3% in the adherent category and 66.7% in the non-adherent category. The results of the chi-square test using SPSS software were obtained with a value of pValue=0.000 with α <0.05, so it can be concluded that there is a relationship between family support and adherence to taking medication after stroke in the elderly.